Assessing The Efficiency Of Two Improved Lesser Known Kilns And Their Effect On The Quality And Shelf Life Of Smoked Fish In Ghana - Asamoah, E.K. (University of Ghana, 2019)
Fish smoking is a traditional fish preservation method which is affordable, and hence employed in most developing countries with logistical challenges in preserving fresh fish for marketing. Smoked fish is a major source of protein in the diets of Ghanaians. Often traditional kilns, that rely on firewood as a source of fuel, are used. These kilns have been shown to be less fuel efficient and the smoked products have high levels of polycyclic aromatic hydrocarbons (PAHs), which are of public health concern. Additionally, poor storage of the products leads to quality losses. This study, which contributes to the search for a more efficient and safe smoking oven, therefore sought to test and compare the efficiency of two improved, but lesser known kilns, the Cabin and Abuesi gas fish smoker (AGFS) to the traditional Chorkor smoker by investigating the physicochemical, microbial and sensory qualities of the smoked products. Finally, the effect of irradiation and different storage conditions on the shelf life of the smoked products was studied. The research was undertaken in Abuesi, in the Western Region, using two marine fish species, the chub mackerel and barracuda. The results showed that the AGFS had 12% lower yield but 86% and 60% higher processing rate than the cabin and Chorkor kilns respectively. Again, the fuel consumption was 68% and 54% better than the Cabin and Chorkor respectively, while the Cabin also saved 29% more fuel than the Chorkor. In terms of the fuel costs, the Cabin was 38% and 54% lower than the Chorkor and AGFS respectively (owing to the lower cost of firewood, compared to LPG). The cost of construction was however extremely high in the AGFS than the Cabin and Chorkor kilns, however, its industrial size (500 kg capacity), faster smoking time and lower fuel consumption make it good alternative to consider. Smoking improved the physical, chemical, microbiological and sensory quality of mackerel and barracuda. These qualities, except for colour and sensory analysis, could not be statistically differentiated between the products from the AGFS and Cabin kiln. The Cabin-smoked products had the more traditional qualities of smoked fish (appearance, odour and flavour), while the gas-smoked products had a pronounced fried appearance and taste. The AGFS produced smoked products with mean benzo(a)pyrene and PAH4 concentrations below the EU MLs (2 and 12 μg/kg respectively). Depending on the type of firewood used, the Cabin also produced benzo(a)pyrene below the MLs when C. mildbraedii (Esa) was used, while the Chorkor had levels 3 to 8 times higher than the MLS. The PAH4 levels in the Cabin and Chorkor products were all above the MLs (4 and 8 times higher respectively). Based on the frequency and quantities of smoked mackerel and barracuda consumed by an average Ghanaian adult (with a life expectancy of 63 years), the potential carcinogenic risks were of least concern in the gas smoked and all barracuda samples (about 1 in 100,000 adults), moderate in the Cabin smoked mackerel (3 and 6 in 100,000 adults) and high in the Chorkor smoked mackerel (7 and 17 in 100,000 adults). Heavy metal (Hg, Pb and Cd) contamination was negligible in fresh and smoked mackerel and barracuda. The effect of irradiation and storage temperature on the quality and shelf life of smoked mackerel showed that irradiation did not affect the nutritional quality (protein, fat, moisture and ash contents) after 65 days of refrigerated storage. The fatty and amino acid compositions were also unaffected by irradiation. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) respectively constituting about 8% and 18% of the total fatty acids. The essential amino acids also contributed about 59% of the total amino acid concentrations. The non-irradiated and irradiated smoked mackerel, stored at refrigerated temperature, were of good microbial and chemical quality by Day 65 of storage, even though lipid oxidation and hydrolysis were affected. Keeping the non-irradiated and irradiated smoked fish at room temperature were rejected by Day 5 of storage due to insect infestation and visible mouldiness (even though most microbial and chemical qualities were good). The results, therefore, indicates that The AGFS performed better, overall, followed by the Cabin and then the Chorkor. The kilns produced fish with good nutritional qualities. Irradiation did not negatively impact on the quality of the smoked products during the 65 days of storage, but refrigerated storage is key to maintaining quality of irradiated fish
PhD. Fisheries Science
Keywords: Ghana; Smoked Fish; Improved; docosahexaenoic acid